Pemahaman Pegawai Kantor Pengadilan Negeri Tentang Asuransi Syariah (Studi Kasus di Kantor Pengadilan Negeri Rantauprapat) - Iis Herike (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
Sharia insurance is a risk management arrangement that complies with sharia provisions. The development of sharia institutions in Indonesia has been very rapid, be it insurance or banking institutions and other businesses based on sharia priciples. The success of an insurance company can be seen from the community’s participation in the importance of company. However, there are still many people who do not understand sharia insurance. So the author is interested in analyzing the understand of employees at the TPH Office of the Provincial Government of sub- district office Rantauprapat about sharia insurance. This study aims to determine the understanding of employees at the district court office Rantauprapat about sharia insurance. This study aims to determine the understanding of employees at the district court office Rantauprapat about sharia insurance. The research method used in this research is descriptive qualitative.